The Influence of Perceived Ease of Use, Perceived Usefulness and Trust on Interest in Using Seabank Digital Bank in Mojokerto City - Aldy Dwi Saputro; Maharani Ikaningtyas (Lavish Opulent Education, 2025)
This study discusses complaints from Seabank users and potential Seabank users on social media regarding applications that are difficult to use, doubts about the security of data and funds and the benefits obtained that can hinder the continuation of Seabank positive trend. This study aims to analyze the effect of Perceived Ease of Use, Perceived Usefulness and Trust on Interest in Using Seabank Digital Bank. Using a quantitative approach, data was collected through a questionnaire with a Likert scale from Seabank Users in Mojokerto City. This study uses multiple linear regression analysis using SPSS. The results showed that Perceived Ease of Use, Perceived Usefulness and Trust simultaneously had a significant effect on Interest in Using, where these variables explained part of the variance in Interest in Using. Individual analysis showed that Perceived Usefulness and Trust had a significant positive effect on Interest in Using, while Perceived Ease of Use did not show a significant effect. These findings suggest that SeaBank should focus more on increasing service benefits and building customer trust rather than relying solely on ease of use in its marketing and product development strategies. This study contributes to research on digital marketing, user behavior in the adoption of financial technology, and strategies for increasing the adoption of digital banking services in Indonesia.